URANIUM GEOCHEMISTRY AND DATING OF PACIFIC ISLAND APATITE - Roe K.K.; Burnett W.C. (My University, 1985)
Uranium-series disequilibrium dating of island phosphate deposits is evaluated in terms of known associated coral ages, uranium geochemistry, and stratigraphic sequences as well as the concordance between the geochronometers , and . U(VI) is the predominant oxidation state of uranium in island phosphorites and by analogy to the youngest surficial deposits, most of the uranium initially bound is in the form of U(VI) sorbed by surfaces from seawater. Insular deposits contain more organic matter than even very young ocean floor samples and this leads to a greater probability of reduction of available recoil uranium than occurs in marine deposits. As a consequence, R(VI) ⩽ R(T) ⩽ R(VI), where R represents the activity ratio. This situation is completely opposite from that observed for marine-origin phosphorites. We determined that a fraction of U(VI) in ancient insular phosphorites is very labile and lost to alkaline carbonate solutions with a uranium activity ratio even more depleted in 234U than the bulk R(VI).Most younger samples appear to have no more discordance between , and than marine phosphorites of similar apparent age. Young, surficial atoll-rim apatite cements and unconsolidated phosphorites date in the range of 1500–8000 years B.P., consistent with the concept of partial submergence of low-lying coral islands prior to 2000 years B.P. Sub-surficial samples in the same environment date older at about 20,000 years B.P. Violation of the closed system assumption occurs in at least 6 out of 13 ancient (> 800,000 year) samples. Uranium-series disequilibrium dating of insular apatite shows some promise as a recorder of climatic/sea level events, but the assumptions necessary for valid ages must be carefully evaluated for each occurrence.